Soft X‐ray Ptychographic Imaging and Morphological Quantification of Calcium Silicate Hydrates (C–S–H). Issue 12 (26th August 2015) - Bae, Sungchul; Taylor, Rae; Shapiro, David; Denes, Peter; Joseph, John; Celestre, Rich; Marchesini, Stefano; Padmore, Howard; Tyliszczak, Tolek; Warwick, Tony; Kilcoyne, David; Levitz, Pierre; et al.
Abstract : Morphological details of calcium silicate hydrate (C–S–H) stemming from the hydration process of Portland cement (PC) phases are crucial for understanding the PC‐based systems but are still only partially known. Here we introduce the first soft X‐ray ptychographic imaging of tricalcium silicate (C3 S) hydration products. The results are compared using both scanning transmission X‐ray and electron transmission microscopy data. The evidence shows that ptychography is a powerful method to visualize the details of outer and inner product C–S–H of fully hydrated C3 S, which have fibrillar and an interglobular structure with average void sizes of 20 nm, respectively. The high‐resolution ptychrography image enables us to perform morphological quantification of C–S–H, and, for the first time, to possibly distinguish the contributions of inner and outer product C–S–H to the small angle scattering of cement paste. The results indicate that the outer product C–S–H is mainly responsible for the q −3 regime, whereas the inner product C–S–H transitions to a q −2 regime. Various hypotheses are discussed to explain these regimes.